Observational Results of Electron Density and Temperature in the Polar Ionosphere by S-210JA-20 and 21 Rockets (e. Event Session) (Proceedings of the Second Symposium on Coordinated Observations of the Ionosphere and the Magnetosphere in the Polar Regions : Part II) - Shigeru MIYAZAKI; Hirotaka MORI; Tadahiko OGAWA (National Institute of Polar Research, 1980)
Two sounding rockets, S-210JA-20 and 21, were launched into the disturbed ionosphere from Syowa Station, Antarctica, in the winter of 1976 for measuring electron density and temperature. Enhancement of the E region electron density of about 5×10^5/cm^3 at 115 km and the electron temperature of about 1100 K around 100 km were observed by S-210JA-20. Maximum electron density of about 2×10^5/cm^3 around 110 km and the electron temperature of about 1000 K around 110 km were observed by S-210JA-21.